Microbial Risk Assessment of Citrus and Carrot Juices - Mudgil, Sandeep (My University, 2007)
The microbiological profile of fresh squeezed kinnow and carrot juices sold through street vended outlets in Patiala, revealed significant loads of total aerobic bacteria, faecal coliforms and staphylococcus. Analysis of same lots of carrots and kinnows throughout the transport chain showed similar loads. Coagulase positve S.aureus (13% of samples of carrot juices) was detected kinnow and carrots samples whereas Salmonella enterica (5% of carrot and kinnow samples) and E.Coli O157:H7 was detected (presumptively) in carrot juice samples from three areas. The non -pathogenic variant of the Salmonella ( LT2, Rif nal) survived well both at 40C and 8oC till 72 hours in kinnow juice samples. The E.coli O157:H7 surrogate strain was unable to grow in carrot juice samples for extended periods of time viz, beyond 48hours and showed significant decline in counts after this time period- in kinnow juice samples the decline was less as compared to that in carrot juice. No significant decrease in counts of E.Coli O157:H7 surrogate strain was observed in carrot juices supplemented with additives after 48 hours. Acid stressed E.coli O157:H7 was able to survive better in kinnow juice samples than its unstressed counterpart till 10 hours. Growth kinetics of inherent spoilage microorganisms in both carrot and kinnow juices indicated that both juices were completely spoiled after 6 hours at 280C. The results of this study highlight the potential risk of fresh squeezed carrot and kinnow juices contaminated with either Salmonella or E.Coli O157:H7 to the consumers within the time frame of spoilage at 280C.
Keywords: citrus and carrot juices; staphylococcus aureus; bacterial pathogens; salmonella; smac; imvic test